Kepala Desa Perempuan dan Local Strongman: Membunuh Atau Menyuburkan Patriarki di Desa Cijaku Kecamatan Cijaku Kabupaten Lebak - W. Wawan; Mohamad Iyos Rosyid (Politicos: Jurnal Politik Dan Pemerintahan, 2023)
This article attempts to dissect the election and leadership of women village heads in Cijaku Village by also examining the role of the Local Stongman behind them. Where in an effort to dissect and explore the topic in this paper the author uses several theoretical studies including Joel S. Migdal's theory of Local Strongman and also studies of women's leadership theory. This research used a descriptive qualitative method with interviews and participatory observation. This research resulted in findings in the form of the influence of Local Strongman in Heni Hendrawati's victory as the female village head in Cijaku village. This role was very significant because it succeeded in breaking the chain of leadership from male actors which gave rise to a female leader with a relatively very young age during the victory in the first period, but this victory was also not spared from the role of men as Local Strongman who mobilized the masses by the control he has, the Local Strongman here is Heni's father, known as Ama Ekeng. So the presence of a female village head in Cijaku Village actually used the role of the patriarchy to garner political power. In terms of leadership as a woman, researchers found a finding from direct observation in the form of very little new programs or innovations from Heni Hendrawati to attract women's participation. In fact, the presence of women leaders in Cijaku Village did not make any significant changes, especially in women's empowerment issues or policies. Even when he was the village head for two terms, he never used his authority to make village-scale regulations.